The Effect of Cat Whisker Leaf Extract (Orthosiphon aristatus) on Estrus Cycle Recovery of Mice (Mus musculus L.) - Musaddad; Ramadhan Sumarmin (Jurnal Serambi Biologi, 2021)
This study aims to determine the effect of Kumis Kucing (Orthosiphon aristatus) leaf extract on the restoration of the estrous cycle of mice (Mus musculus) which has been induced by extending the estrous cycle with angsana stem bark extract (Pterocarpus indicus Wild). This study used a vaginal smear method or vaginal smear which was observed at 10.00 a.m to determine the phase of the estrous cycle for 24 days. Mice were divided into 4 treatment groups with 6 repetitions. The treatments were T1 (control), T2 (0.035 mg / head / day), T3 (0.135 mg / head / day), and T4 (0.175 mg / head / day). The data analiyzed using Analysis of Variance (ANOVA) and the DNMRT at p<0.05. The results showed O. aritatus the length of the estrous cycle were at T1 5.26; T2 6.5; T3 5.74; and T4 4.54 days. At T1, T3, and T4 have found that the estrous cycle was normal. But, the T2 is still in an extended state. It can be concluded that O. aristatus leaf extract can restore the estrous cycle of mice.